Analisis Literatur Mengenai Penggunaan Attribute Sampling Sebagai Alat Bantu Auditor Dalam Pengujian Kepatuhan Dan Pengendalian Internal - Fhebi Ramayanti; Elyanti Rosmanidar; Suci Rahwa Wati; Rahmatul Hasanah; Putri Murni; Muhammad Dwi Afrizal (ICONS: Islamic Economics Journal, 2025)
This study is a literature analysis that discusses the use of attribute sampling as one of the statistical sampling techniques applied by auditors in compliance testing and internal control assessment. Attribute sampling enables auditors to evaluate the degree of adherence to established procedures by examining sample transactions representing the population. This technique is widely used because it provides sufficient assurance regarding the effectiveness of an entity’s internal control system. This study aims to identify the basic concepts, advantages, limitations, and relevance of attribute sampling in modern audit practices. This research employs a literature review method by analyzing journal articles, audit textbooks, and the latest auditing guidelines. The results of the analysis show that although attribute sampling is effective for compliance testing, auditors must consider sampling and non-sampling risks and ensure that sample determination procedures are appropriately performed so that audit results are valid and reliable. This study is expected to serve as a reference for academics and audit practitioners to understand the important role of attribute sampling in supporting audit quality.